Phytochemical and toxicological evoluation of drt leaves of Cynara scolymus (Research, Society and Development, 2021)
Indications for the use of medicinal plants for the cure, prevention and treatment of diseases, since ancient times, serve as an important source of information for the search for compounds with therapeutic properties. Cynara scolymus plant, known as Artichoke, presents itself as a vegetable low in calories, rich in fiber and iron, low in fat, carbohydrates, mostly formed by inulin, it is indicated in diets for diabetics and people with constipation, obesity and is also recommended as an anti-anemic. Given these therapeutic indications, this work aims to identify the phytochemical profile in the hydroalcoholic extract and toxicological analysis for in vitro methemoglobin evaluation in the hydroalcoholic and aqueous artichoke extracts. The sample for analysis was acquired from an herbalist in the city of Belém, in the state of Pará, all analyzes were performed in triplicate. The results found for qualitative phytochemical analysis indicated positive for Alkaloids, Triterpenes, Tannins/Phenols and Saponins, the other identifications of metabolites were negative; on the other hand, the results of methemoglobin toxicity in the hydroalcoholic extract at all concentrations showed percentages above the permitted level, and in the aqueous extract, only two concentrations of 600 µg/mL and 500 µg/mL were acceptable for the human body. It is concluded that artichoke has therapeutic activity, but also presented a high percentage of methemoglobin toxicity.